Students’ satisfaction on facilities in Universiti Utara Malaysia - Ideris, Muhamad Shah Kamal; Lim, Ting Yi; Mohd Rodzi, Safarina; Romle, Abd Rahim; Mohamad Zabri, Mohd Akmal Hakim; Mahamad, Nor Azlindamazlini (International digital organization for scientific information (IDOSI), 2016)
Service quality is one of the most important criteria to measure consumers’ satisfaction.They are not only concerned with how a service is being delivered but also with the quality of output they received.Positive perception on quality of services being delivered occurs when it exceeded customers’ expectation.A review of the literature revealed that the general description of service quality attributes are (a) tangible,(b) reliability, (c) responsiveness, (d) assurance and (e) empathy.For the purpose of indicating student’s satisfaction on the service quality of facilities in UUM, questionnaires have been distributed to students at University Utara Malaysia to explore their perception.Results from the survey were examined to see whether there is any relationship between the five service quality attributes and students’ satisfaction.